Incidental Idiopathic Proximal Tibial Distal Fibular Synostosis: An Unusual Case Report - Shah, Arvind; Sahu, Bikramjit (Annapurna Journal of Health Sciences, 2024)
Tibiofibular Synostosis is one of the rare causes of pain in the knee joint. Conservative treatment is the recommended treatment of choice. A 30-year-old male footballer came to our clinic complaining of knee joint pain, with no history of trauma. Pain is increasing on walking, no abnormality was detected, but a marginal increase in the girth of the left calf muscle compared to the contralateral right side. Imagine results revealed Proximal Tibial-Distal Fibular Synostosis